Vertically Oriented 2D Layered Perovskite Solar Cells with Enhanced Efficiency and Good Stability. Issue 33 (10th July 2017) - Zhang, Xinqian; Wu, Gang; Yang, Shida; Fu, Weifei; Zhang, Zhongqiang; Chen, Chen; Liu, Wenqing; Yan, Jielin; Yang, Weitao; Chen, Hongzheng
Abstract : Vertically oriented highly crystalline 2D layered (BA)2 (MA) n −1 Pb n I3 n +1 (BA = CH3 (CH2 )3 NH3, MA = CH3 NH3, n = 3, 4) perovskite thin‐films are fabricated with the aid of ammonium thiocyanate (NH4 SCN) additive through one‐step spin‐coating process. The humidity‐stability of the film is certified by the almost unchanged X‐ray diffraction patterns after exposed to humid atmosphere ( H r = 55 ± 5%) for 40 d. The photovoltaic devices with the structure of indium tin oxide(ITO)/poly(3, 4‐ethylenedioxythiophene):poly(styrene‐sulfonate)/(BA)2 (MA) n −1 Pb n I3 n +1 ( n = 3, 4)/[6, 6]‐phenyl‐C61 ‐butyric acid methyl ester/Bathocuproine/Ag are fabricated. The devices based on (BA)2 (MA)2 Pb3 I10 perovskite ( n = 3) with the precursor composition of BAI:methylammonium iodide:PbI2 :NH4 SCN = 2:2:3:1 (by molar ratio) show an averaged power conversion efficiency (PCE) of 6.82%. In the case of (BA)2 (MA)3 Pb4 I13 ( n = 4), a higher PCE of 8.79% is achieved. Both of the unsealed devices perform unique stability with almost unchanged PCE during the period of storage in purified N2 glove box. This work provides a simple and effective method to enhance the efficiency of the 2D perovskite solar cell. Abstract : A new route to realize the vertical‐orientation growth of 2D layered (BA)2 (MA) n −1 Pb n I3 n + ( n = 3, 4)‐based perovskite with the aid of a NH4 SCN additive through a one‐step spin‐coating method is presented. The corresponding planar‐structured solar cells present the averaged power conversion efficiency (PCE) of 6.82% ( n = 3) and the best PCE of 8.79% ( n = 4) with unique stability.